ENVIRONMENTAL STRESSORS EXPERIENCED IN CHILDHOOD ARE RELATED TO EMOTIONAL WELL-BEING DECADES LATER. (11th November 2018) - Pasquini, G; Munoz, E; Gamaldo, A; Mogle, J; Sliwinski, M; Scott, S
Abstract: Theory suggests that early adversity may confer risk to well-being, independent of exposure to stressors in adulthood, and that age may moderate this relationship (Cohen et al., 2010; Schilling and Diehl, 2014). This study tests exposure to childhood neighborhood and psychosocial environmental stressors as predictors of emotional well-being in adulthood and whether age moderates the association. Participants (n=194, age 25–65 years) residing in Bronx, New York completed retrospective reports of neighborhood stressors (e.g., noise, violence, graffiti) at age 5 and psychosocial stressors (e.g., parental divorce, substance use, abuse) during childhood along with current emotional well-being (i.e., anxiety, anger, depression, and life satisfaction). Multiple regression results indicated that participants reporting more exposure to psychosocial stressors in childhood reported higher current anxiety (p<.01), anger (p<.001), and depression (p<.01), and lower ratings of life satisfaction (p<.05). Unexpectedly, more exposure to neighborhood stressors at age 5 predicted lower anxiety, anger, and depression in adulthood (p's<.05). Participants reporting more police activity in the neighborhood at age 5 reported more anger (B=2.78, SE=1.36, p<.05). Older age was associated with fewer symptoms of anxiety (B=-0.15, SE=0.06, p<.05) and anger (B=-0.20, SE=0.07, p<.01), but the associations between neighborhood and psychosocial stressors on adult well-being outcomes did not vary by current age (p's >.30). All models covaried for current and childhood socio-economic status. These findings are consistent with theorized persistent effects of childhood psychosocial stressors and poorer emotional functioning in adulthood, however results for childhood neighborhood stressors are mixed.